REFLEKSI NILAI “MOPO’O TANGGALO DUHELO” DI BALIK PENDAPATAN OLEH KUSIR BENDI: STUDI ETNOMETODOLOGI ISLAM - Mohamad Anwar Thalib (UIN Sunan Gunung Djati Bandung, 2023)
Abstract This study aims to reflect on the local cultural values behind the practice of income accounting by bendi drivers. This study uses an Islamic paradigm with an Islamic ethnomethodological approach. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy. The results of the study found that the way the bendi drivers earn income when they are at the base is through something other than a queuing or lane system. Prospective passengers are free to choose which buggy they want to rent. The income accounting practice is conditional on local cultural values in the form of “mopo’o tanggalo duhelo”